Using a spatial resilience lens to understand alignments and misalignments in South Africa's marine governance system - Hardisty, Shannon (Rhodes University, Faculty of Science, Department of Environmental Science, 2020)
In marine protected areas (MPAs), the radically open nature of marine ecosystems, the seemingly contradictory short-term goals of fisheries management (resource use) and conservation efforts (biodiversity protection), the variety of stakeholders, and the inherently political nature of space ha ve contributed to a disconnect between policy and practice. Many groups operate in an MPA at various spatial and socio-political scales, from national government bodies to local community groups, as such an MPA can be viewed as a complex, multi-scale and multi-level social-ecological system (SES). A greater understanding of the multi-scale processes driving the spatial resilience of SES can help address scale mismatches between continuous ecological change and the long-term governance of a seascape. South Africa has a long history of spaces and natural resources being politicised and faces high levels of unemployment and political frustration. Marine governance has been characterised as being siloed, lacking transparency regarding government processes and even between departments, and not properly addressing the needs of local communities; resulting in scale and level mismatches throughout the multi-scale processes (from national policies to local regulations)therefore, it is pertinent to understand the interactions between various national policies, their implementation, and their impacts. Using a spatial resilience lens, I set out to understand scale alignment in South Africa's marine governance systems as it relates to MPAs. A spatial resilience lens emphasises analysis of both spatial and temporal scales, thus highlighting the multi-scale variables and interactions that occur within a system. I first sought to understand the policy and management across national and regional scales by conducting a series of semi-structured interviews with experts which were analysed using thematic analysis. I then approached the question of alignment from a local to national scale by using the Table Mountain National Park Marine Protected Area as a case study, here I carried out a series of workshops and interviews with line fishers, women's groups, and eco-tourism operators from three different communities. Experts identified six themes when describing the structure of gove rnance in South African MPAs; they consisted of: government departments and marine legislation, management level factors, communication and information sharing, local level factors, biophysical factors, and scale. Communication and information sharing was the most mentioned referenced theme (40.26 %). The relationships between the communities and other actors (i.e. how communities are impacted, or impact on, the Department of Environmental Affairs , the Department of Agriculture Forestry and Fisheries, and Park Authorities) contributed 67.27 % to the total number of mentions, 91 % of which were from the following themes: communication and information sharing, local level factors, biophysical factors, and scale. My results indicate that weak, top-down relationships dominate the governance system in South Africa. During the Cape Town workshops I applied the spatial resilience lens in three ways. Firstly, the participants collaborated on a mapping exercise discussing the existing zone types within the MPA, as well as developing their own. There was an 87.87 % overlap of community designed zones on the existing MPA zones, however the types of zones designed by the community were different. Secondly, I carried out a document analysis and used information from the workshops to analyse the status and rights designation of important species for different user groups. The results show that the various stakeholder groups, while all active in the marine environment, interact with the ecosystem at different scales and with differing species. The differing interactions between groups result in challenges such as representation and complicated power dynamics between user groups. Finally, I asked participants to discuss factors that affect their ability to gain a livelihood from the sea. The external elements and their effects differed between the user groups, identifying important socio-political interactions. Whilst the external elements were all geographically distinct and localised, the spatial resilience lens allowed for a cross-scale, and to a certain extent cross-sector, understanding of these elements thus producing a more holistic understanding. My thesis shows that user groups operate on different spatial scales within the marine environment as a result of social, economic, and political influences leading to several scale-based challenges. The identified scale-based challenges have contributed to misalignments in marine governance in South Africa. My study shows that scale mismatches have important implications for understanding how marine policy influences user groups and identified pathways that affected policy implementation , and identifies future research application of a spatial resilience lens within social-ecological systems, for example it's potential use in understanding the gendered nature of MPAs
Keywords: Marine parks and reserves -- South Africa; Marine parks and reserves -- South Africa -- Management; Marine parks and reserves -- Government policy -- South Africa; Table Mountain National Park (South Africa); Spatial ecology -- South Africa; Coastal zone management -- South Africa